High: drugs, desire, and a nation of users - Walker, Ingrid (University of Washington Press, 2017)
Preface: Breaking user silence -- Acknowledgments -- Introduction: We are all users -- Picture a drug user -- Criminalization : winning the crusade but losing the war -- Medicalization : defining drug use -- Why we use : the pleasure and the eros of drugs -- Conclusion -- Notes -- Glossary -- Selected bibliography -- Index